Waqf and Environment: A Bibliometric Analysis - Muhammad Syariful Anam; Rasikh Saifan Ahmad; Reza Awaliah Ali; Rina Rosia (Shirkah: Journal of Economics and Business, 2022)
Despite the plethora of studies on environmental waqf in the literature, research objectives and results are still inconsistent. Therefore, this study maps the literature on environmental waqf to explore future research directions. Based on data from Scopus from 2001 to March 2022, bibliometric analysis using VOSviewer was used to create this mapping research system. This study visualized a map of co-authorship and co-occurrence of keywords. We present several aspects of the literature on environmental waqf, such as the number of publications per year, document type, journal, author, affiliation, country, subject, and topic. The environmental waqf research review is made up of 120 articles written by 160 authors who are affiliated withÂ 116 institutions across 29 countries. These articles were published in 79 sources. The bibliometric results through the analysis of the keywords identified four research streams: waqf in sustainable development, regional planning, waqf governance in the agricultural sector, and cash waqf for welfare improvement. This study proposesÂ future directions for environmental waqf research, focusing on the role of waqf in achieving the goal of sustainable development for environmental stability.